Spatio-Temporal Urban Growth Patterns In The Colombo Urban Fringe, Sri Lanka - Weerakoon, Katupulle Gedera Padma Kumari (2017)
Rapid urbanisation and urban growth, in particular, in the developing world require a scientific understanding of spatio-temporal urban growth patterns. This knowledge is highly essential for sustainable land management and urban development planning. Modern GIS technologies have opened up great opportunities in monitoring and managing fast urban growth. However, these techniques have some limitations in decision making for sustainable development. Spatio-temporal urban growth occurs due to changes of the main urban system comprising physical, socio-economic, and environmental subsystems.